Influence of the external torques in the angle between the spin axis and the Sun direction for spin stabilized satellite - Motta, G. B. [UNESP]; Zanardi, M. C. (IOP Publishing, 2015)
The goal of this paper is the study of the influence of the environmental torques in the angle between the spin axis and the Sun direction (solar aspect angle) for spin stabilized satellite. The theory uses a cylindrical satellite in an illumined orbit, considering the gravity gradient, aerodynamic, solar radiation, residual magnetic and eddy current torques. The mathematic model for each torque is shown. The dynamic equations are represented in a reference system fixed in the satellite and described by spin velocity and the right ascension and declination angles of the spin axis. An analytical solution for the spin velocity and the attitude angles is used to study the behavior of the solar aspect angle. The theory is applied for the real data of the Brazilian Satellite of Data Collection - SCD1 and SCD2. Two approaches are presented. The results agree with the real satellite behavior for specific time simulation. Then the theory has consistency and can be applied to predict the behavior of the solar aspect angle.